2015
DOI: 10.1007/s00221-015-4267-z
|View full text |Cite
|
Sign up to set email alerts
|

Music, clicks, and their imaginations favor differently the event-based timing component for rhythmic movements

Abstract: The involvement or noninvolvement of a clock-like neural process, an effector-independent representation of the time intervals to produce, is described as the essential difference between event-based and emergent timing. In a previous work (Bravi et al. in Exp Brain Res 232:1663-1675, 2014a. doi: 10.1007/s00221-014-3845-9 ), we studied repetitive isochronous wrist's flexion-extensions (IWFEs), performed while minimizing visual and tactile information, to clarify whether non-temporal and temporal characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…The setup is fully described elsewhere [5][6][7] and is summarized here. Each participant was tested individually, sitting upright on a chair with the feet on a leg rest, and wearing an eye mask (to prevent interference from visual information) and headphones (to reduce environmental noise and to deliver audio information; K 240 Studio, AKG Acoustics GmbH, Wien, AT).…”
Section: Set Upmentioning
confidence: 99%
“…The setup is fully described elsewhere [5][6][7] and is summarized here. Each participant was tested individually, sitting upright on a chair with the feet on a leg rest, and wearing an eye mask (to prevent interference from visual information) and headphones (to reduce environmental noise and to deliver audio information; K 240 Studio, AKG Acoustics GmbH, Wien, AT).…”
Section: Set Upmentioning
confidence: 99%
“…Recently, our group has devoted attention to improve the understanding of how KT is able to modulate motor control, and namely the variability, of a rhythmic motor behavior. We investigated the effect of KT application on timing coordination in healthy individuals by studying repeated isochronous wrist’s flexion-extensions (IWFEs) performed with no direct surface opposition and while minimizing visual information (Bravi et al, 2014a , b , 2015 , 2016 ). We showed that KT, when applied on the dominant arm, was able to reduce timing variability of IWFEs performed under various auditory conditions and during their recall (Bravi et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%
“…We thus performed an experiment in which healthy subjects, tested with KT and without KT (NKT), have participated in two sessions (KT and NKT cases) in which sets of IWFEs were performed with the DL and the NDL, in a synchronization-continuation task at the two inter-onset intervals (IOIs) of 550-ms and 800-ms. As in our previous studies (Bravi et al, 2014a , b , 2015 , 2016 ) participants were asked to perform movements in a natural way (Huys et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The setup is the same we used in our previous works [3][4][5][6][7] and is here summarized. Every participant was tested individually, sitting upright on a chair with the feet on leg rest.…”
Section: Setupmentioning
confidence: 99%
“…The extra-proprioceptive hypothesis is plausible since in our experimental paradigm IWFEs were performed with no direct surface opposition and while minimizing visual information, thus accentuating the role of sensory information that provides limb position and movement senses to produce rhythmic actions as accurate as possible [3][4][5][6][7]. Studies investigating proprioception have found that not all healthy subjects are endowed with same proprioceptive ability [9,40].…”
Section: Introductionmentioning
confidence: 99%